Mechanism of administrative and legal regulation of the use of personal data by local governments - Havrylyuk, Ruslana (Amazonia Investiga, 2021)
The article is devoted to studying the peculiarities of the mechanism of administrative and legal regulation of the use of personal data by local governments. The authors focus on the organizational, legal, and administrative- procedural principles of using personal data by local governments in Ukraine. The international experience of legal regulation of personal data use is analyzed. The purpose of the study was to determine the characteristics of the mechanism of administrative and legal regulation of the use of personal data by local governments. According to the purpose, the object of the study is the public relations that arise in the field of the use of personal data by local governments. And the subject of the study is the mechanism of administrative and legal regulation of such use. The methodological basis of the study is a set of general and unique methods of cognition, in particular: dialectical, historical, descriptive, methodology of scientific analysis, and generalization - comparative law, structuralfunctional and analytical. The authors made conclusions that to improve national legislation, Ukraine, under its obligations under the Association Agreement with the EU, must implement mechanisms for the appropriate level of protection of personal data.
Механізм адміністративно-правового регулювання використання персональних даних органами місцевого самоврядування
Keywords: information on restricted access; personal data; protection of personal data; administrative and legal mechanism; local governments